Female Resistance in Ek Chihan Novel - Wagle, Manendra (Academia Research Journal, 2023)
Feminist theory is the method of study about women's ecomomic, social, political status based on society, family and various cultural value and beliefs. With the development of Western literature, its influence has increased tremendously along with its entry into world literature. The article is based on Hridaychandra Singh Pradhan's Ek Chihan novel and its narration on women's exploitation at family, society & economic and their resistance as the subject of the study. Marxist feminism is main basis for the analysis of the novel. The library is used for the collection of materials and the novel is analyzed by creating an analysis framework from the collected materials. The novel analyzes the unequal treatment of a husband towards his wife, sexual exploitation of a young woman by enticement and lure and patriachal male mentality. The novel summarizes the perspective for the women to act against all types of injustices and oppression against them.